METODE AL-BAYAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AWAL AL-QUR’AN ANAK USIA DINI: AL-BAYAN METHOD TO IMPROVE THE BEGINNING READING ABILITY OF EARLY CHILDREN'S AL-QUR'AN - Setiawan, Eko (Universitas Islam Malang, 2020)
The purpose of this study was to determine the application of the Al-Bayan method in improving the ability to read early Al-Qur'an in RA Ar Rohman Batu City. This research is a classroom action research. Techniques using of data collecting are observation, learning outcomes, and documentation. This research was conducted in 2 cycles, with 5 meetings each cycle. The research subjects were students of group A RA Ar Rohman with a total of 23 students. The results showed that learning Al-Qur'an using the Al-Bayan method has increased, with the results in the first cycle the average learning outcomes of BSH children (developing as expected) and the second cycle increasing with the average learning outcomes of BSB (developing as expected). ). Thus, the application of the Al-Bayan method can improve the ability to read the early A-Qur'an group A students aged 4-5 years.